Analysis of Language Errors on The Thematic Semester Final Examination Problems 1 and 2 Elementary School Level - Ayu Puspita Indah Sari; Mardhotillah Mardhotillah (JETL (Journal of Education, Teaching and Learning), 2023)
In the 2013 curriculum, which applies integrated thematic learning, Indonesian plays an essential role as a vehicle for carrying knowledge, from being a means of communication and a means of thinking. Therefore, language errors must be minimized in teaching and learning. This study aims to describe the types of errors and the causes of errors in writing the Final Semester Examination questions in Thematic 1 and Thematic 2. This research was carried out at Baitur Rahmah Elementary School. This type of research is descriptive qualitative research. Data collection methods used are observation and interviews. The data analysis technique was carried out through three stages: note, listen, and record. This research uses data source and method triangulation to test data validity. The study results illustrate that there are still many spelling, word, and sentence errors. This is caused by several sources, namely the last educational background of the teacher who teaches, the lack of understanding of the rules in writing, and the lack of accuracy in making the questions.